Advanced Hydrodynamic Modelling of Flow at a River Bridge: Insights from 3D Computational Fluid Dynamics - Lazzarin, Tommaso; Constantinescu, George; Viero, Daniele P. (Procedia Structural Integrity, 2024)
Failure of river bridges is often due to hydraulic reasons, such as the development of severe scouring around piers and abutments. In many cases, the presence of bridge structures produces complex flow fields, which are difficult to predict using standard hydraulic models. This entails difficulties in estimating the hydrodynamic actions on the structure and the potential scour on the riverbed. A three-dimensional Computational Fluid Dynamics (3D CFD) model is used to analyze the flow field and the bed shear stresses at an existing bridge. The Volume of Fluid (VoF) method allows resolving the deformable free-surface, and the Detached Eddy Simulation (DES) approach allows resolving the dynamics of the energetically important turbulent eddies in the flow. The analysis deals with modeling the flow around a realistic, full-scale, multi-pier bridge in the Po River. Simulations considered different hydrodynamic regimes, i.e., the free-surface flow regime and the hypothetical pressure-flow regime which would occur when water levels are higher than the low chord of the bridge deck. The numerical application highlights the potential of the DES technique for analyzing the hydrodynamics of flow at bridges in natural river channels. Besides the turbulent flow fields and the description of the vortical structures, relevant results include the time-varying spatial distribution of the hydrodynamic forces acting on the different parts of the bridge and the time-varying distribution of the shear stress on the bed. This aspect is of particular interest because i) the estimation of drag forces on the structure components may be oversimplified using canonical, averaged formulas, and ii) the fluctuations in time of the bed shear stresses play a key role in determining the removal of sediments from the bed and the scour hole close to the bridge piers.